2017
DOI: 10.1002/cncr.30624
|View full text |Cite
|
Sign up to set email alerts
|

Acute lymphoblastic leukemia in adolescents and young adults

Abstract: Acute lymphoblastic leukemia (ALL) in the adolescent and young adult (AYA) population is a difficult clinical problem. The AYA population, generally regarded as patients aged 15 to 39 years, currently draws a good deal of attention, particularly in the area of therapy selection. The current trend is to treat this group of patients with leukemia regimens based on pediatric protocols, and results comparing pediatric approaches versus adult approaches to treatment are maturing. Results are pending from a large US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 45 publications
1
31
0
1
Order By: Relevance
“…In the past decade, the treatment of ALL has made significant progress in understanding the pathogenesis of disease, predicting prognosis, and developing new therapies. The application of targeted therapy significantly improved the survival of patients with ALL [5-8]. Further improvements in the outcome of ALL therapy require the development of novel, targeted and low toxic therapies.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the treatment of ALL has made significant progress in understanding the pathogenesis of disease, predicting prognosis, and developing new therapies. The application of targeted therapy significantly improved the survival of patients with ALL [5-8]. Further improvements in the outcome of ALL therapy require the development of novel, targeted and low toxic therapies.…”
Section: Introductionmentioning
confidence: 99%
“…This was the case with the hyper-CVAD regimen (hyper-fractionated cyclophosphamide, vincristine, doxorubicin [Adriamycin], and dexamethasone alternating with methotrexate and cytarabine) and the pediatric regimens applied to adolescents and young adults. 89,90 The difference in outcome between adult and pediatric patients with ALL is attributable to 4 subcategories that have different incidences in the 2 age groups. [88][89][90][91] ALL with hyperdiploid karyotype and ETS variant 6-runt-related transcription factor 1 (ETV6-RUNX1) translocations, both of which are favorable categories, constitute 25% each of pediatric ALL but <5% each of adults.…”
Section: Acute Lymphocytic Leukemiamentioning
confidence: 99%
“…89,90 The difference in outcome between adult and pediatric patients with ALL is attributable to 4 subcategories that have different incidences in the 2 age groups. [88][89][90][91] ALL with hyperdiploid karyotype and ETS variant 6-runt-related transcription factor 1 (ETV6-RUNX1) translocations, both of which are favorable categories, constitute 25% each of pediatric ALL but <5% each of adults. Ph-positive ALL, an entity with an unfavorable prognosis until recently, comprises 25% of adult ALL but only 5% of pediatric cases.…”
Section: Acute Lymphocytic Leukemiamentioning
confidence: 99%
“…This suggests that for these 8 patients, pediatric oncologists were involved in comanaging the care of patients diagnosed between ages 15 and 18 years with their adult oncology colleagues via multicenter tumor boards or other avenues of communication that were not captured in our data sources, and/or that patients or physicians traveled between different centers. It has been shown that some AYA patients with cancer, such as those diagnosed with acute lymphoblastic leukemia, have improved event‐free and overall survival when treated with pediatric protocols, although a minority of AYA patients with acute lymphoblastic leukemia receive pediatric regimens . A recent study found improved outcomes for AYA patients with HL who are treated with a pediatric protocol compared with those treated with an adult protocol .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that some AYA patients with cancer, such as those diagnosed with acute lymphoblastic leukemia, have improved event-free and overall survival when treated with pediatric protocols, 34,35 although a minority of AYA patients with acute lymphoblastic leukemia receive pediatric regimens. 36 A recent study found improved outcomes for AYA patients with HL who are treated with a pediatric protocol compared with those treated with an adult protocol. 37,38 The results of the current study suggest that treatment by a pediatric oncologist is associated with a higher likelihood of receiving recommended posttreatment care, although this occurred among a small number of patients.…”
Section: Discussionmentioning
confidence: 99%